Age and reasons for first dental visit in a tertiary care hospital in South India - Shini Susan Samuel; Grace Rebekah (Wolters Kluwer Medknow Publications, 2021)
Background: Early visit to the dentist with an aim of prevention has been advocated universally, but the timing for seeking dental treatment differs among different countries. Aim: This study aimed to determine the timing and reasons for the first dental visit among children attending the dental clinic in a tertiary care hospital in Tamil Nadu, South India. Methods: This hospital-based study reviewed the dental records of children who had visited the dental clinic from January 1, 2019 to December 31, 2019. All those between 0 and 10 years of age and visiting a dentist for the first time were included in the study. The continuous variables were analyzed using mean and standard deviation. The categorical variables were calculated using Chi-square, Fisher's exact test, and two-proportion test. Results: We reviewed the dental records of 1005 children (60% boys and 40% girls). The most frequent age for the first dental visit was between 5 and 6 years. The most common reasons for visits to the dental clinic were pain (23.8%) and dental caries (16.6%). Only 3.8% of children had their first dental visit by 1 year of age and primarily for therapeutic purposes. Dental caries and traumatic injuries were more frequent in children below the age of 3 years. Conclusion: The present study found pain as the most frequent reason for the visit, but there was a delay in first dental visits among children. This study suggests effective oral health policies for children and a need to change the perception and practices among the dental professionals in the region. Timing of the first dental visit of a child can help us to determine the quality of dental care a child receives. Delayed dental visit among children in this study indicates the ineffective oral health policies and the gap that exists between the pediatric health-care providers in India.